Penggunaan Media Sosial Instagram Sebagai Media Pemasaran Bisnis Kuliner pada Komunitas Online @deliciousbali - I Putu Hendika Permana; Ni Kadek Ayu Natalia Pratiwi (JUSTBEST: Journal of Sustainable Business and Management, 2021)
Instagram is a social media that is used to share photos and has begun to be widely used for marketing communication purposes with its characteristics that can provide visual messages and high interactivity. Marketing using social media is popular, especially in the culinary field. One of them is @deliciousbali account that uses Instagram to give reviews about culinary and promote it. This study aims to find out how to use Instagram as a culinary information and promotion media with case studies on the online community @deliciousbali. This research uses descriptive research method. Data obtained from the study documentation upload account @deliciousbali. The results of this study are in promotion through social media Instagram shows that Instagram has features that six aspects of The 7C Framework namely aspects of context, content, community, communication, connection, and commerce.